The Response of Living Organisms to Low Radiation Environment and Its Implications in Radiation Protection - Belli, Mauro; Indovina, Luca (Frontiers in Public Health, 2020)
Life has evolved on Earth for about 4 billion years in the presence of the natural background of ionizing radiation. Without it, life on Earth could not have existed or would not exist in the present form. Even if today the natural background radiation is extremely small (few mSv/y), nevertheless it may be significant enough for living organisms to sense it and respond to it, also keeping memory of this exposure. A better understanding of this response is relevant not only for improving our knowledge on life evolution, but also for assessing the robustness of the present radiation protection system at low doses, such as those typically encountered in every day life. Given the large uncertainties in epidemiological data below 100 mSv, quantitative evaluation of these health risk is currently obtained with the aid of radiobiological models. These predict a health detriment, caused by radiation-induced genetic mutations, linearly related to the dose. However a number of studies challenged this paradigm by demonstrating the occurrence of non-linear responses at low doses, and of radioinduced epigenetic effects, i.e., heritable changes in genes expression not related to changes in DNA sequence. This review is focused on the role that epigenetic mechanisms, besides the genetic ones, can have in the responses to low dose and protracted exposures, particularly to natural background radiation. Many lines of evidence show that epigenetic modifications are involved in non-linear responses relevant to low doses, such as non-targeted effects and adaptive response, and that genetic and epigenetic effects share, in part, a common origin: the reactive oxygen species generated by ionizing radiation. Cell response to low doses of ionizing radiation appears more complex then that assumed for radiation protection purposes and that it is not always detrimental. Experiments conducted in underground laboratories with very low background radiation have even suggested positive effects of this background. Studying the changes occurring in various living organisms at reduced radiation background, besides giving information on the life evolution, have opened a new avenue to answer whether low doses are detrimental or beneficial, and to understand the relevance of radiobiological results to radiation protection